Endometriosis, a modern syndrome - Brosens, Ivo (Medknow Publications, 2011)
The identification of endometriosis has been a subject of intense debate over the last decade. There is, however, no doubt that Thomas Cullen was the first to describe endometriosis and adenomyosis as one disease characterized by the presence of endometrium-like tissue outside the uterine cavity. With the introduction of laparoscopy in the early 1960s three different clinical presentations of endometriosis were distinguished: peritoneal, deep adenomyotic and cystic ovarian. As soon as synthetic steroids became available, pioneer clinicians started utilizing these in an attempt to replace radical surgery by a medical treatment. While medical therapy may resort in relief, in most cases the current approach consists of a combination of medical and surgical therapy. While the pathogenesis of endometriosis is still enigmatic and complex, there is increasing evidence that endometriosis is part of a uterine reproductive dysfunction syndrome. For prevention of complications, it is very important that diagnosis is made as early as possible in a woman's life.